2022
DOI: 10.3390/insects13050406
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and Biogeographic History of Parnassius Butterflies (Papilionidae: Parnassiinae) Reveal Their Origin and Deep Diversification in West China

Abstract: We studied 239 imagoes of 12 Parnassius species collected from the mountains of the Qinghai–Tibet Plateau (QTP) and its neighbouring areas in China. We selected three mitochondrial gene (COI, ND1, and ND5) sequences, along with the homologous gene sequences of other Parnassius species from GenBank, to reconstruct the phylogenetic tree and biogeographic history of this genus. Our results show that Parnassius comprises eight monophyletic subgenera, with subgenus Parnassius at the basal position; the genus crown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…Most current studies of biogeography use the same method to analyse spatial aspects of evolution (adopting a priori areas and using one or more "ancestral area" algorithms), and the same method to establish the time line of evolution (using fossil calibrations to give maximum clade ages). This is seen in many recent studies on Lepidoptera (for example, Kodandaramaiah et al, 2018;Toussaint et al, 2019Toussaint et al, , 2021aToussaint et al, , 2021bCrews and Esposito, 2020;Chazot et al, 2021;Krupitsky et al, 2021;Matos-Marav ı et al, 2021;Usami et al, 2021;Zhao et al, 2022;St Laurent et al, 2023). Biogeography would benefit from a greater diversity of approaches, as the current methods of area analysis and dating analysis have serious shortcomings (see introductory sections, above).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most current studies of biogeography use the same method to analyse spatial aspects of evolution (adopting a priori areas and using one or more "ancestral area" algorithms), and the same method to establish the time line of evolution (using fossil calibrations to give maximum clade ages). This is seen in many recent studies on Lepidoptera (for example, Kodandaramaiah et al, 2018;Toussaint et al, 2019Toussaint et al, , 2021aToussaint et al, , 2021bCrews and Esposito, 2020;Chazot et al, 2021;Krupitsky et al, 2021;Matos-Marav ı et al, 2021;Usami et al, 2021;Zhao et al, 2022;St Laurent et al, 2023). Biogeography would benefit from a greater diversity of approaches, as the current methods of area analysis and dating analysis have serious shortcomings (see introductory sections, above).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these drawbacks, most current studies of biogeographic evolution rely on the ancestral-area algorithms and do not examine the details of distribution or even map the recovered clades (e.g. for butterflies, Kodandaramaiah et al, 2018;Toussaint et al, 2019Toussaint et al, , 2021aToussaint et al, , 2021bChazot et al, 2021;Condamine et al, 2023;Krupitsky et al, 2021;Matos-Marav ı et al, 2021;Usami et al, 2021;Zhao et al, 2022). Instead, the distributions are analysed with respect to a small number of large, a priori regions, the small number being imposed by computational limits.…”
Section: Methodological Problems In the Spatial Analysis Of Evolutionmentioning
confidence: 99%
“…We only used trees containing at least 50% of the valid species in the correspondent clade (electronic supplementary material, table S12). For the majority of butterflies and amphibians, we relied on two recently published super-trees [60,61], but for specific butterfly lineages underrepresented in the super-tree, we used complementary phylogenies [62][63][64][65]. To include Alpine species that were absent from these trees, we performed additional calibrations using secondary calibration points.…”
Section: Methodsmentioning
confidence: 99%
“…The genus Parnassius is a typical mountain-adapted butterfly group, mainly distributed across the Holarctic, with its highest diversity on the Qinghai–Tibet Plateau (QTP) and adjacent mountainous regions (including Xinjiang and Gansu, China), with a broad elevational range of 3000–5000 m ( Figure 1 ). Previous studies have indicated that the diversification of Parnassius initiated during the Middle Miocene, correlated with their host plant’s spatiotemporal distributions, and geological and paleoenvironmental changes in the QTP region [ 12 , 13 ], as well as the fact that both the ancient gene introgression and climate cooling after the Middle Miocene Climate Optimum (MMCO) might have contributed to the spread of Parnassius species to different altitudes, accompanied by the dispersal from West China to Northeast China and other areas of East Asia [ 14 ]. Among them, the Glacial Apollo butterfly, Parnassius glacialis , is the only species that has dispersed into the southeastern areas of the Yangtze River, and mainly inhabits low-altitude mountains (~200 to 1800 m), suggesting their extraordinary flexibility to local seasonal environmental challenges.…”
Section: Introductionmentioning
confidence: 99%